(untitled) (Research, Society and Development, 2020)
The systematic review is an essential method for collecting data on a particular object of study. It is a type of research that requires a strict protocol for searching, collecting, analyzing and presenting data, with or without the use of statistical methods. In this sense, Graph Theory is one of the branches of mathematics that offers important resources for the analysis and representation of the relationships between variables of any nature, being also very useful in research such as systematic reviews in the field of psychology. This article is an innovative methodological proposal that aims to describe: the basic process of construction, interpretation and the use of graphs in systematic reviews applied to the area of psychology. The results indicate that with the use of search techniques with graphs it is possible to view and identify rules of association between keywords, for example, in addition to assisting in the investigation of the relationships between the variables under study. It is concluded that the techniques of analysis and visualization by means of graphs, as well as the application of a centrality measure, proved to be adequate and effective, being able to contribute to systematic review studies.